Knowledge-defined intent-based network autonomy - Jingyu WANG; Cheng ZHOU; Lei ZHANG; Cong LIU; Zirui ZHUANG; Hongwei YANG; Danyang CHEN; Yanhong ZHU; Lu LU; Jianxin LIAO (Dianxin kexue)
The complexity of the network determines that the autonomy of the intention network can’t be achieved at one go.The key is to break through multiple problem domains of network management and control from a global perspective, to summarize the network rules, mechanisms and strategies into knowledge, to build the knowledge space of resource allocation in the whole scene, and finally to realize the ubiquitous intelligence of the intention network.Focusing on 6G intention network, which takes knowledge-defined intelligence as the key enabling technology to improve the perception and decision-making closed-loop ability of intention network, and constructs a self-learning, self-operating and self-maintaining intention network.Achieving full autonomy in 6G networks is a long-term goal, which requires step by step evolvements, from providing repeat operation alternatives, to performing perception and monitoring on network environment and equipment states, to making decisions according to a number of factors and strategies, to effectively sensing end-user experience, and finally to a fully autonomous intelligent network that senses the intention of operators and users, self-optimizes and self-evolves.